The Political Economy Of Climate Resilience: A Cross-Country Evaluation Of Policy Innovation, Green Finance, And Sustainable Productivity Dynamics - Saripah (Journal of Global Economic Development and Policy, 2025)
This article investigates the political economy of climate resilience through a cross-country evaluation of policy innovation, green finance mechanisms, and sustainable productivity dynamics that shape global responses to the climate crisis. Employing a comparative approach grounded in macroeconomic indicators and national policy frameworks from low-, middle-, and high-income countries, this study examines how policy configurations, institutional capacities, and regulatory architectures influence the effectiveness of transitions toward low-carbon economies. The findings reveal that policy innovation serves not only as a catalyst for adaptation and mitigation but also as a stabilizing force for macroeconomic performance when integrated with credible green finance instruments. Furthermore, countries that successfully internalize circular economy principles and low-emission technologies demonstrate long-term productivity gains without compromising ecological balance. The study concludes that climate resilience emerges from the complex interplay between political structures, policy design, and financial capacity. These insights offer strategic implications for governments and international institutions seeking to formulate integrative policies that enhance economic resilience while promoting sustainable development.